Seismic risk assessment and hazard mapping in Nepal - Chaulagain, Hemchandra
Seismic risk in the form of impending disaster has been seen from past records that moderate-to-large earthquakes have caused the loss of life and property in all parts of Nepal. Despite the availability of new data, and methodological improvements, the available seismic hazard map of Nepal is about two decades old. So an updated seismic hazard model at the country level is imperative and logical. The seismic hazard and risk model constitute important tools for framing public policies toward land-use planning, building regulations, insurance, and emergency preparedness. In fact, the reliable estimation of seismic hazard and risk eventually minimizes social and economic disruption caused by earthquakes. In this frame of reference, the seismic risk assessment at a country level is elementary in reducing potential losses stemming from future earthquakes. Thus, this study investigates structural vulnerability, seismic risk, and the resulting possible economic losses owing to future earthquakes in Nepal. To this end, seismic risk assessment in Nepal is done using an existing probabilistic seismic hazard, a newly developed structural vulnerability, and recently released exposure data. The OpenQuake-engine, the open-source platform for seismic hazard and risk assessment from the Global Earthquake Model initiative, was used to calculate the seismic hazard and risk in Nepal. The seismic hazard and mean economic loss map were formulated for the 1, 2, 5, and 10 % probability of exceedance in 50 years. Finally, the distribution of building damage and corresponding economic losses due to the recurrence of the historical 1934 earthquake was presented in this study.